GBA1 Thr408Met mutation in a patient with Parkinson’s disease - Yi ZHAO; Junwen LI; Chunlian JU; Weibin QIU; Bo ZUO; Zhigang YANG; Yansheng LI (Zhongguo Linchuang Yixue, 2025)
GBA1 gene mutation is an important genetic risk factor for Parkinson’s disease (PD). This paper reports a case of a 43-year-old male PD patient carrying a rare heterozygous Thr408Met mutation in the GBA1 gene identified through whole-exome sequencing, leading to a diagnosis of GBA1-associated PD. The patient’s motor symptoms were primarily characterized by bradykinesia and rigidity, without significant cognitive decline. Treatment with low-dose levodopa combined with a dopamine agonist resulted in significant symptomatic improvement.